Electroluminescence of Colloidal Quantum Dots in Electrical Contact with Metallic Nanoparticles. Issue 2 (4th December 2017) - Wang, Hongyue; Le‐Van, Quynh; Aassime, Abdelhanin; Roux, Xavier Le; Charra, Fabrice; Chauvin, Nicolas; Degiron, Aloyse
Abstract: The electroluminescence of a carpet of colloidal quantum dots in electrical contact with a metal nanoparticle array is investigated. The properties of the structures spectacularly differ from the well‐known behavior of point sources placed at nonvanishing distances from subwavelength scatterers (robustness to quenching, coupling primarily defined by the electrical contact between the two species, etc.). This regime of short‐range interactions can even be enabled with nonplasmonic inclusions made of platinum, providing an extreme case of enhanced and tailored light emission by quantum emitters in a highly absorptive environment. As a corollary, surface plasmons are not a necessary or sufficient ingredient but add functionalities that nonplasmonic structures do not possess. These findings indicate that the physics of localized light emitters in highly inhomogeneous environments is far from being fully understood and have important implications for the next generation of active metamaterials and advanced optoelectronic devices. Abstract : The electroluminescence of colloidal quantum dots exhibits unexpected and technology‐enabling properties when the emitters are brought in electrical contact with metallic nanoparticles. The hybridization between the two species is robust to quenching, goes beyond plasmonics, and opens up new paths for active metamaterials and other advanced optoelectronic devices.